2008
DOI: 10.1016/j.jacc.2007.12.053
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological Study on the Effect of Pre-Hypertension and Family History of Hypertension on Cardiac Autonomic Function

Abstract: Our study provides evidence that CAF plays a role in pre-hypertension and that altered autonomic function is already present in subjects with FHH. An autonomic imbalance shifting with augmented sympathetic tone was more enhanced in pre-hypertension.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
41
2
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(49 citation statements)
references
References 27 publications
4
41
2
2
Order By: Relevance
“…Similar results are obtained by Shenoy et al [5] However, Devrath et al [6] and Wu et al [7] have shown decreased parasympathetic activity in offsprings of hypertensive parents. Table No.…”
Section: Discussionsupporting
confidence: 88%
“…Similar results are obtained by Shenoy et al [5] However, Devrath et al [6] and Wu et al [7] have shown decreased parasympathetic activity in offsprings of hypertensive parents. Table No.…”
Section: Discussionsupporting
confidence: 88%
“…A significant reduction in HRV measurements was seen in all groups, from no risk factor normotensives to hypertensives (17). In the hypertensive patients in our study, no statistically significant effect of family risk factors were seen on the parameters of HRV.…”
Section: Resultscontrasting
confidence: 40%
“…According to an epidemiological study which included 1436 hypertensive, prehypertensive and normotensive patients and subjects, hypertensive and prehypertensive patients had decreased HRV measurements compared to normotensive individuals, and similarly hypertensives had lower measurements compared to prehypertensives (17). In our study, no significant difference was observed between patients previously treated for hypertension and those newly diagnosed hypertensives in terms of demographic, clinical and laboratory inability to obtain a sufficient number of patients and a lack of grouping by treatment drug seems to be important limitations of the current study.…”
Section: Türk Nefroloji Diyaliz Ve Transplantasyon Dergisi Turkish Nementioning
confidence: 99%
“…The power component of this frequency part can be calculated as an absolute power by power spectral density (PSD) graphics, such as in Figure 1. The LF and HF power values can be given in a normalized form as a result of the proportion of each power component value and the value obtained by subtracting the power value belonging to the VLF band from the total power [14]. It has been verified by other studies that the power value of the HF component varies according to the parasympathetic effects completely [13][14][15].…”
Section: Signal Processingmentioning
confidence: 99%